THE POLICY OF THE FORMULATION OF DEATH PENALTY AGAINST PERPETRATORS OF CORRUPTION - ., Indrawati (2015)
The policy of the formulation of death penalty against perpetrators of corruption should be implemented quickly, given that corruption as an extraordinary crime and which carries massive seriousness has become a systemic crime and even has a destructive impact on the world , and therefore should be given the heaviest penalty, i.e. the death penalty. The current Corruption Eradication Act has not established the criteria of corruption with specific seriousness, as well as the minimum limit of the specified amount which is punishable by death penalty. This limitation of norm needs to be addressed by comparing it with the provisions of the corruption acts in China and Thailand which have explicitly established death penalty to eradicate corruption in their nations. Therefore, it is time for Indonesia to improve the Corruption Act by including provisions of a strict death penalty to minimize corruption in Indonesia. Keywords: Formulation Policy, Corruption, Extraordinary Crime, Death Penalt